(untitled) (Tempo e Argumento, 2024)
This article examines the epistemological proposal of Nuestra Orilla podcast, an eight-episode audio series resulting from a participatory research process, carried out in collaboration between historians, communicators, and two Afro-Colombian social leaders from the Bajo Atrato region in the Colombian Pacific. The series, also hosted on a website where history unfolds through a curation of primary and secondary sources, tells the history of the Colombian region of Bajo Atrato from the perspective of its inhabitants and through the narrator’s life experience: Ana Luisa Ramírez. This project aimed to produce a history (regarded as a critical method of inquiry and as a narrative genre at the same time) of this region of the Colombian Pacific that challenges the places, temporalities, and methodologies used to tell the stories of violence in Colombia, with the hope of producing counter-histories that help repair the way we relate to each other and to the environment.